Analysis of the Effect of Climate Change on Rice Production in Nigeria - Opeyemi Gbenga; Opaluwa Haruna Ibrahim; Olowogbayi Jonathan Ayodele (Hasanuddin University, 2020)
The Nigerian economy largely depends on agriculture which is vulnerable to unfavorable climatic conditions. Consequently, rice is a very important staple crop, widely cultivated and consume by millions of people in the country. Nigerian government policy heavily protects rice in order to stimulate it local production. There is still scanty empirical evidence on the effect of climate change on rice production in Nigeria. This study was carried out to fill this gap. This study specifically examined the effect of climate change on rice output in Nigeria. This study utilized climate data (rainfall and temperature) from Nigerian Meteorological Center, Carbon dioxide data from FAOSTAT, and information on the country’s` milled rice from USDA (1970-2016). The analytical tools employed in the data analysis were Descriptive, Trend analysis, Unit root test, Co-integration and Regression model. Findings of the study revealed that there is variation in the trend of the climatic factors and also variation in rice output over the period of study. The result also shows that that annual rainfall, and temperature contributes significantly to rice output in Nigeria. Rainfall had positive coefficient and significant 5%, temperature had negative coefficient and significant at 1%. The area of land cultivated had positive coefficient and significant at 1%. The study concluded that climate change significantly influence rice output in Nigeria. The study recommended that consideration be given to climate change in the formulation of agricultural policies for the attainment of food security and national aspiration for sustainability in the production of rice production in Nigeria.